Survival and growth of Japanese cedar (Cryptomeria japonica) planted in tree shelters to prevent deer browsing: a case study in southwestern Japan. Issue 3 (4th May 2022) - Nomiya, Haruto; Abe, Tetsuto; Kanetani, Seiichi; Yamagawa, Hiromi; Otani, Tatsuya; Sakai, Atsushi; Yoneda, Reiji
ABSTRACT: Tree shelters are used in forestry to prevent large herbivores from browsing on young trees. Although tree shelters can generally prevent browsing damage while the young trees are within the tree shelters, they have been observed to fail in some cases. In this study, to clarify the protective capacity of tree shelters against damage due to deer browsing, the condition of tree shelters on planted Japanese cedar ( Cryptomeria japonica ) seedlings 2 to 7 years after installation was investigated at 42 sites in southwestern Japan where the density of sika deer ( Cervus nippon ) is high. The results showed that tree shelters failed for three reasons. Firstly, the shelter had collapsed or incline and could no longer protect the saplings within. Secondly, the saplings in the shelters died relatively shortly after they were planted. Thirdly, and possibly most importantly, the saplings are browsed upon by deer after they extended beyond the top of the shelter. Since there was no correlation between the damage rate and the number of years after planting, it is likely that the damage occurred immediately after the young trees protruded form the shelter. Shelters with a height of only 140 cm, which are widely used in Japan, may be too short to completely prevent herbivory damage by deer.